To the Gut Microbiome and Beyond: The Brain-First or Body-First Hypothesis in Parkinson’s Disease - Nuzum, Nathan D.; Loughman, Amy; Szymlek-Gay, Ewa A.; Teo, Wei-Peng; Hendy, Ashlee M.; Macpherson, Helen (Frontiers in Microbiology, 2022)
There is continued debate regarding Parkinson’s disease etiology and whether it originates in the brain or begins in the gut. Recently, evidence has been provided for both, with Parkinson’s disease onset presenting as either a ‘body-first’ or ‘brain-first’ progression. Most research indicates those with Parkinson’s disease have an altered gut microbiome compared to controls. However, some studies do not report gut microbiome differences, potentially due to the brain or body-first progression type. Based on the etiology of each proposed progression, individuals with the body-first progression may exhibit altered gut microbiomes, i.e., where short chain fatty acid producing bacteria are reduced, while the brain-first progression may not. Future microbiome research should consider this hypothesis and investigate whether gut microbiome differences exist between each type of progression. This may further elucidate the impact of the gut microbiome in Parkinson’s disease and show how it may not be homogenous across individuals with Parkinson’s disease.